2006
DOI: 10.1021/ed083p622
|View full text |Cite
|
Sign up to set email alerts
|

What Happens When Chemical Compounds Are Added to Water? An Introduction to the Model-Observe-Reflect-Explain (MORE) Thinking Frame

Abstract: This article describes a laboratory module designed to help students understand how different compounds behave when they are dissolved in water. Students measure the conductivities of various aqueous solutions using handheld conductivity testers with LED displays. By counting the number of LEDs illuminated, students can differentiate between electrolytes and nonelectrolytes and approximate the relative numbers of ions in solution. This enables students to discover how ionic compounds dissociate when dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 11 publications
0
34
1
Order By: Relevance
“…All students interviewed completed a laboratory module entitled "What happens when chemical compounds are added to water?" (subsequently referred to as the "dissolution module"), in which they investigated the molecular-level behaviour of compounds dissolved in water (Mattox, Reisner, & Rickey, 2006). Students measured the conductivities of various aqueous solutions, including sodium chloride (NaCl(aq)).…”
Section: Participants and Instructional Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…All students interviewed completed a laboratory module entitled "What happens when chemical compounds are added to water?" (subsequently referred to as the "dissolution module"), in which they investigated the molecular-level behaviour of compounds dissolved in water (Mattox, Reisner, & Rickey, 2006). Students measured the conductivities of various aqueous solutions, including sodium chloride (NaCl(aq)).…”
Section: Participants and Instructional Contextsmentioning
confidence: 99%
“…As part of the dissolution module, each student submitted an initial model (as a prelaboratory assignment) and a final refined model of their molecular-level views of aqueous solutions (Mattox et al, 2006;Tien et al, 2007). We assessed students' understanding of the molecular-level behaviour of ionic and molecular compounds dissolved in water prior to the interview via the final refined laboratory models they constructed for the dissolution module at the beginning of their first-semester general chemistry courses.…”
Section: Pre-interview Data and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different kinds of assignments have been used to promote metacognition in chemistry learning (Rickey & Stacy, 2000). These include the deliberate use of a thinking frame (Mattox, Reisner, & Rickey, 2006), student documentation of thinking through heuristics such as concept maps (Francisco, Nakhleh, Nurrenbern, & Miller, 2002; Novak & Gowin, 1984; Selvaratnam & Canagaratna 2008), student work in extended problem‐solving situations (Cooper, Sandi‐Urena, & Stevens, 2008b) and work in using extended writing within laboratory work (Burke, Greenbowe, & Hand, 2006; Greenbowe & Hand, 2005; Hand, Wallace, & Yang, 2004; Walker, Sampson, & Zimmerman, 2011; Wink & Choe, 2008). Larson and Middlecamp (2003) also reported on how pre‐elementary education majors benefited from activities that allowed for additional reflection on course topics within a companion course to a general education chemistry course.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has shown that instructional paradigms in which students fi rst work to develop general rules or models, and expert ideas are presented only after students complete their investigations, promote deep understandings that facilitate transfer of learning [e.g., (6)]. Research in the context of another MORE module (7) indicates that student engagement in three thinking processes is strongly correlated with subsequent successful reasoning in new contexts. These include (i) constructing molecularlevel models that are consistent with experimental evidence, (ii) refl ecting accurately and completely on how one's own molecularlevel ideas changed relative to previous ideas, and (iii) identifying evidence to justify model refi nements as part of the refl ection on how and why ideas changed.…”
mentioning
confidence: 99%